2012
DOI: 10.1097/ccm.0b013e3182374828
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model for simulating daily bed occupancy in an intensive care unit*

Abstract: It is possible to develop simulation models that can be used to predict future intensive care unit resource needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 26 publications
(25 reference statements)
0
19
0
4
Order By: Relevance
“…Prior studies have developed models to simulate varying hospital unit sizes, nurse or physician staffing levels, and different triage, discharge, and bed assignment policies to examine the impact on bed use, wait times, lengths of stay, readmissions, and mortality (17)(18)(19)(20)(21)(22). Although many models capture patient flow through multidisciplinary ICUs (23), often with elective admissions (24), no studies included both an ICU and SDU with patients with different acuity levels within a single model. This study's aim is to present a framework for understanding and improving patient flow through the medical ICU and SDU, and to present illustrative analysis for a single hospital.…”
mentioning
confidence: 99%
“…Prior studies have developed models to simulate varying hospital unit sizes, nurse or physician staffing levels, and different triage, discharge, and bed assignment policies to examine the impact on bed use, wait times, lengths of stay, readmissions, and mortality (17)(18)(19)(20)(21)(22). Although many models capture patient flow through multidisciplinary ICUs (23), often with elective admissions (24), no studies included both an ICU and SDU with patients with different acuity levels within a single model. This study's aim is to present a framework for understanding and improving patient flow through the medical ICU and SDU, and to present illustrative analysis for a single hospital.…”
mentioning
confidence: 99%
“…The taskforce further recognized that any physician staffing model may still get overwhelmed in times of high patient volume or acuity and may, at other times, seem to be overstaffed. There is clearly a need to develop tools to better predict both the regularity and the severity of surges and such modeling has already been proposed by some (63). Nevertheless, a good staffing model would recognize that these high-volume days occur with some measurable frequency and be able to handle the increased workload without significant compromise in patient care.…”
Section: Recommendationsmentioning
confidence: 97%
“…An exception is the model developed by Griffin et al [21] which focuses on obstetric unit patient discharge times sampled from an empirical probability distribution of discharge times. Barado et al [22] developed a statistical model for simulating patient occupancy in an intensive care unit and found that inclusion of length of stay and discharging rules was critical to the success of the simulation. Cohen et al [23] account for regular and emergent transfers between units, but they assume that LOS at a unit is independent of the unit from which the patient arrived.…”
Section: Previous Approaches To Bed Capacity Decisionsmentioning
confidence: 99%